NGS analysis of nasopharyngeal microbiota in SARS-CoV-2 positive patients during the first year of the pandemic in the Campania Region of Italy. (April 2022) - Giugliano, Rosa; Sellitto, Assunta; Ferravante, Carlo; Rocco, Teresa; D'Agostino, Ylenia; Alexandrova, Elena; Lamberti, Jessica; Palumbo, Domenico; Galdiero, Massimiliano; Vaccaro, Emilia; Pagliano, Pasquale; Weisz, Alessandro; et al.
Abstract: Since its first appearance, the SARS-CoV-2 has spread rapidly in the human population, reaching the pandemic scale with >280 million confirmed infections and more than 5 million deaths to date (https://covid19.who.int/ ). These data justify the urgent need to enhance our understanding of SARS-CoV-2 effects in the respiratory system, including those linked to co-infections. The principal aim of our study is to investigate existing correlations in the nasopharynx between the bacterial community, potential pathogens, and SARS-CoV-2 infection. The main aim of this study was to provide evidence pointing to possible relationships between components of the bacterial community and SARS-CoV-2 in the nasopharynx. Meta-transcriptomic profiling of the nasopharyngeal microbial community was carried out in 89 SARS-Cov-2 positive subjects from the Campania Region in Italy. To this end, RNA extracted from nasopharyngeal swabs collected at different times during the initial phases of the pandemic was analyzed by Next-Generation Sequencing (NGS). Results show a consistently high presence of members of the Proteobacteria (41.85%), Firmicutes (28.54%), and Actinobacteria (16.10%) phyla, and an inverted correlation between the host microbiome, co-infectious bacteria, and super-potential pathogens such as Staphylococcus aureus, Klebsiella pneumoniae, Streptococcus pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, and Neisseria gonorrhoeae. In depth characterization of microbiota composition in the nasopharynx can provide clues to understand its potential contribution to the clinical phenotype of Covid-19, clarifying the interaction between SARS-Cov-2 and the bacterial flora of the host, and highlighting its dysbiosis and the presence of pathogens that could affect the patient's disease progression and outcome. Highlights: SARS-CoV-2 infection is associated with a dysbiosis of the microbiota and a higher risk of bacterial co-infection. Microbiota characterization is important for identifying bacterial species associated with increased COVID-19 disease severity. The meta-transcriptomic analysis can be useful to guide clinical management of the COVID-19 patients.